2022
DOI: 10.3390/foods12010069
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental C Addressed the pH Conundrum in Sustainable Marine Aquaponic Food Production Systems

Abstract: pH is the major issue that concerns all producers in aquaponics, as the main three organisms (aquatic animal, plant, and microbes) have different preferences. Additional C is a potential approach to amend the growing environment and improve shrimp and plant growth, and microbe establishment. Aquaponics under saline conditions has, however, not been studied in detail in regard to the effect of pH and additional C. In this study, we evaluate the impact of pH and additional C on the growth of Pacific whiteleg shr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Aquaponic nutrient solutions are not as easy to maintain as hydroponic solutions. The aquaponic solution is affected by many factors, such as fish feeding rate, hydraulic loading rate, and pH [10,11]. Yang and Kim [2] analyzed three different feeding rates and found that a uniform feeding rate can enhance crop yield and/or quality in aquaponics by increasing initial nutrient availability and overall nitrogen-use efficiency of the system [2].…”
Section: Introductionmentioning
confidence: 99%
“…Aquaponic nutrient solutions are not as easy to maintain as hydroponic solutions. The aquaponic solution is affected by many factors, such as fish feeding rate, hydraulic loading rate, and pH [10,11]. Yang and Kim [2] analyzed three different feeding rates and found that a uniform feeding rate can enhance crop yield and/or quality in aquaponics by increasing initial nutrient availability and overall nitrogen-use efficiency of the system [2].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal pH for ammonia and nitrite oxidizing bacteria is 7.3-8.0. We described this challenge as the "pH conundrum" [4]. Aquatic animals tend to be tolerant of pH ranges outside optimal, but suboptimal pH for plants can reduce nutrient uptake from the environment.…”
Section: Opinionmentioning
confidence: 99%
“…Aquatic animals tend to be tolerant of pH ranges outside optimal, but suboptimal pH for plants can reduce nutrient uptake from the environment. Using a flocponic system (biofloc is a term describing the purposeful addition and maintenance of a complex bacterial community and use of biofloc approaches in aquaponics has been termed flocponics) with Pacific white shrimp and red orache, minutina, Swiss chard, okahijiki, and kale, we identified that some plants overcame decreased growth at pH 7.5 when additional carbon was added to the system [4]. Further research is needed in the area of optimal water quality that optimizes healthy populations of all three taxa.…”
Section: Opinionmentioning
confidence: 99%
“…The prospects of using both technologies in Ukraine and the positive environmental and economic conditions were discussed by Y.-T. Chu et al (2023). They noted that there are various methods of hydroponics, such as drip irrigation techniques, film systems and root immersion systems, which help to precisely control the nutrition of plants and create optimal conditions for their growth.…”
Section: Introductionmentioning
confidence: 99%